La responsabilidad internacional de los Estados por anular o no reconocer laudos - Cantuarias Salaverry, Fernando; Repetto Deville, Jose Luis (Pontificia Universidad Católica del Perú, 2014)
In the framework of international treaties, with special emphasis on theBilateral investment treaty (Bit), various responsibilities for states that comprise arise. However , what happens when the courts of a country interfere contrary to international standards in full force and effect of an award, the impact caused in that state and that leading to be internationally liable to a Bit or FtA are studied in this essay. the author further analyze jurisprudence of investment arbitration tribunals in cases Saipem v. Bangladesh, ATA v. Jordan Frontier Petroleum v. Czech Republic and White Industries v. India, also focuses on the case of Peru; and urges members of a treaty respect the rules of the game.

En el marco de los tratados internacionales, con especial énfasis en el tratado Bilateral de inversión (Bit), surgen diversas responsabilidades para los estados que lo conforman. sin embargo, el qué ocurre cuando los órganos jurisdiccionales de un país interfieren contrariamente a los estándares internacionales en plena validez y eficacia de un laudo y la repercusión que ocasionan en tal estado y que lo conllevan a ser responsable internacionalmente frente a un Bit o un tLC, son tratados en este artículo. el autor, además de analizar jurisprudencia de los tribunales arbitrales de inversiones en los casos Saipem v. Bangladesh, ATA v. Jordania, Frontier Petroleum v. República Checa y White Industries v. India, se centra también en el caso peruano; e insta a quelos países miembros de un tratado respeten las reglas del juego.
The international responsibility of States due to cancel or not to recognize awards
Keywords: Law; Bilateral Investment Treaty; States; International Responsibility; Judicial Bodies; Arbitral Award; Tratado Bilateral De Inversión; Estados; Responsabilidad Internacional; Instancias Jurisdiccionales; Laudo Arbitral; https://purl.org/pe-repo/ocde/ford#5.05.00